Business Incubation for People with Severe Mental Illness Histories: The Experience of One Model. Issue 1 (2nd April 2016) - Mandiberg, James M.; Edwards, Michael
ABSTRACT: The Enterprise People was a business incubator for people with serious mental health conditions that operated in Madison, Wisconsin, from 1998–2005. It supported entrepreneurs with learning basic business skills, start-up processes and expenses, back office supports, ongoing problem solving, and for some, with space to conduct their businesses. The original impetus was to discover whether people with SMI histories could successfully start and operate small businesses. Although this was confirmed, the experience also uncovered factors that will allow other projects of this sort to succeed, and some core infrastructural supports that need to be created. The experience demonstrates that self-employment supported by formal business incubation is a viable option in the range of mental health vocational rehabilitation models.